ANALISIS PENGARUH LUAS LAHAN, TENAGA KERJA, DAN JUMLAH PRODUKSI KELAPA SAWIT TERHADAP PDRB SUB SEKTOR PERKEBUNAN DI KABUPATEN LABUHANBATU SELATAN - Yamani, Raisa; Nasution, Hardini Pazriati; Ruslan, Dede; Sari, Raina Linda (ITB AAS Indonesia Surakarta, 2024)
This study aims to investigate the impact of land area, number of workers, and oil palm production on the Gross Regional Domestic Product (GRDP) of plantation sub-sectors in South Labuhanbatu District, North Sumatra Province. The GDP variable of the plantation sub-sector is used as a dependent variable, while land area, number of workers, and oil palm production are used as independent variables. The data used is secondary data from 2011 to 2021 which is interpolated into quarterly data, with a total of 44 data. The analysis method used is Ordinary Least Square (OLS) regression using Eviews 10.0 software. OLS analysis is a development of multiple regression analysis that describes how much influence the independent variable has on the dependent variable. The results of the analysis show that land area, number of workers, and oil palm production have a positive and significant influence on the GRDP of plantation sub-sectors in South Labuhanbatu Regency both partially and simultaneously. Partially, the regression results show that land area has a coefficient of 11.52384 with a probability value of less than 0.05%, the number of workers has a coefficient of 0.300888 with a probability value of less than 0.05%, and oil palm production has a coefficient of 2.222429 with a probability value of less than 0.05%. Simultaneously, the variables of land area, number of workers, and oil palm production contribute 87% to the variable GDP of the plantation sub-sector in South Labuhanbatu Regency. Keywords: Land Area, Labor, Total Production, GRDP, Plantation Sub-Sector, Palm Oil